A new species of Callichirus Stimpson, 1866 (Axiidea, Callianassidae) from the Pleistocene bioclastic sediment of southeast Brazil - Hernáez, Patricio [UNESP]; Buchmann, Francisco Sekiguchi [UNESP]; Santana, William (Elsevier, 2020)
A new species of ghost shrimp, Callichirus santensis sp. nov., is described from the Upper Pleistocene Cananéia Formation, southeast Brazil. The new species is described based upon preserved ischium, carpus, propodus, and dactylus of the male major cheliped. Diagnostic features of the new species include: (i) ischium with distinctive lateral carina; (ii) carpus unarmed; and (iii) cutting edge of dactylus consisting of large subrectangular tooth proximally, large acute tooth centrally, and small blunt teeth distally. The new species represents the first record for the genus from the Pleistocene of Brazil.
Keywords: Callichiridae; Decapoda; Fossorial shrimps; Quaternary; Taxonomy